2022
DOI: 10.1177/17474930221138707
|View full text |Cite
|
Sign up to set email alerts
|

Poor collateral flow with severe hypoperfusion explains worse outcome in acute stroke patients with atrial fibrillation

Abstract: Background: Atrial Fibrillation (AF) is associated with poorer functional outcomes in acute stroke patients. It has been hypothesized that this is due to poor collateral recruitment. Aims: This study aimed to investigate the relationship between AF and collaterals with outcome in thrombectomy patients. Methods: This retrospective cohort study identified 1036 acute ischemic patients from the INternational Stroke Perfusion Imaging REgistry. The cohort was divided into two groups: 432 with AF and 604 without AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…All studies were observational cohort studies, 8 , 10 , 11 , 12 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 comprising 16 096 patients with AIS (mean age, 70.1 years; women, 48.2%; 6862 with AF versus 9234 without AF). Five studies 12 , 23 , 24 , 25 , 27 provided propensity‐score matching data. Seven studies 14 , 21 , 22 , 23 , 25 , 27 , 29 included patients with anterior and posterior circulation occlusions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were observational cohort studies, 8 , 10 , 11 , 12 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 comprising 16 096 patients with AIS (mean age, 70.1 years; women, 48.2%; 6862 with AF versus 9234 without AF). Five studies 12 , 23 , 24 , 25 , 27 provided propensity‐score matching data. Seven studies 14 , 21 , 22 , 23 , 25 , 27 , 29 included patients with anterior and posterior circulation occlusions.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 12 , 23 , 24 , 25 , 27 provided propensity‐score matching data. Seven studies 14 , 21 , 22 , 23 , 25 , 27 , 29 included patients with anterior and posterior circulation occlusions. Eight studies 8 , 10 , 11 , 12 , 26 , 28 , 30 , 31 included patients with anterior circulation occlusions only, 1 study 13 included patients with posterior circulation occlusions only, and 2 studies 20 , 24 did not provide the information of occluded vessels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral anticoagulants also reduce the risk of recurrent stroke in AF patients, which is a substantial source of morbidity and mortality in the setting of AF [105]. Furthermore, there is increasing awareness that poorer collateral perfusion is a predictor that mediates suboptimal clinical outcomes in AIS patients with AF [106][107][108]. A retrospective study revealed that AF was significantly more likely to be present in AIS patients with poor collateral status compared to those with good collateral status [107].…”
Section: Impact Of Atrial Fibrillation On Stroke Outcomesmentioning
confidence: 99%